Hearing Loss Risk in Pediatric Patients Treated with Cranial Irradiation and Cisplatin-Based Chemotherapy - Cohen-Cutler, Sally (Int J Radiat Oncol Biol Phys, 2021)
PURPOSE: Cranial radiation therapy (RT) and cisplatin-based chemotherapy are essential to treating many pediatric cancers but cause significant ototoxicity. The objective of this study is to determine the relationship of RT dose with risk for subsequent hearing loss in pediatric patients treated with cisplatin. METHODS AND MATERIALS: This retrospective study of cisplatin-treated pediatric patients examined ototoxicity from cranial RT. Ototoxicity was graded for each ear according to International Society of Pediatric Oncology (SIOP) consensus ototoxicity scale. RT dose to cochlea was calculated using mean, median, maximum, and minimum dose received to determine most predictive parameter for hearing loss. Multivariable logistic regression models then examined risk factors for hearing loss. RESULTS: In 96 children (161 ears) treated with RT+cisplatin, minimum cochlear RT dose was most predictive of hearing loss. Higher cochlear RT dose was associated with increased hearing loss (Odds Ratio [OR] per 10 Gy dose increase = 1.64, p = 0.043), with added risk in those receiving an autologous bone marrow transplantation (aBMT) (HR = 10.47, p < 0.001). CONCLUSIONS: This research supports further testing of minimum cochlear RT dose as a more predictive dose parameter for risk of ototoxicity. Cochlear RT dose was additive to risk of hearing loss from underlying cisplatin-based chemotherapy. Exposure to aBMT was the strongest predictor of developing hearing loss, placing these children at particularly high risk for hearing loss across all cochlear doses. Future prospective studies are crucial to further inform RT dose thresholds and minimize risk of hearing loss in childhood cancer survivors.